TÍNH CHẤT MÀI MÒN CỦA COMPOZIT TRÊN CƠ SỞ NHỰA POLYESTE KHÔNG NO GIA CƯỜNG BẰNG SỢI ARAMIT NGẮN - Thu, Nguyễn Minh; Diệu, Trần Vĩnh; Lộc, Nguyễn Đức (Vietnam Journal of Chemistry, 2012)
The abrasive weight/volume loss of the unsaturated polyester reinforced by chopped aramid fibers has been investigated. Two methods with and without pressure have used to prepare the samples. The effect of length, length to radius, weight fraction of fiber on abrasive characteristics and various mechanical properties such as tensile strength, modulus, tensile elongation, hardness, impact strength has been discussed. The optimum value of abrasive properties gained at the fiber length of 5.48 µm and fiber content of 6% with the weight abrasive loss reduces 4.09 times compared to unsaturated polyester resin. Wear characteristics of the specimens depends on the conditions. The abrasive weight loss increases with increase of the load and sliding speed.